MOF or COF membranes for olefin/paraffin separation: Current status and future research directions - Wei, Ruicong; Liu, Xiaowei; Lai, Zhiping (Advanced membranes, 2022)
In response to global efforts to combat climate change, many research efforts have contributed to upgrading cryogenic distillation, an energy-intensive petrochemical operation, especially for olefin/paraffin separation. Metal-organic framework (MOF) membranes can be a competitive candidate for this purpose. In this work, we reviewed the main progress of MOF membranes for olefin/paraffin separations, with the main focus on the potential of ZIF-8 for C3H6/C3H8 separation. Membranes of other potential materials, including covalent organic framework (COF) for olefin/paraffin separation, were also reviewed in detail. We then projected our views on searching for next-generation materials for high-performance olefin/paraffin separations. Finally, a guide of future research perspectives was provided to enable the first membrane of olefin/paraffin separation to be commercialized. [Display omitted]